Antioxidant properties of camelina (Camelina sativa (L.) Crantz) protein hydrolysates - Na Thi Ty Ngo; Fereidoon Shahidi (Journal of Food Bioactives, 2021)
Camelina seed meal was used to produce protein hydrolysates using Alcalase and Flavourzyme. The hydrolysates were then fractionated by employing ultrafiltration membranes (3, 10 kDa). The antioxidant activities of camelina protein hydrolysates and peptide fractions were investigated. The essential amino acid content of camelina protein isolates and hydrolysates was comparable and adequate. All camelina hydrolysates exhibited the highest radical scavenging activity in both DPPH and ABTS assay compared to camelina protein isolates. When comparing the overall DPPH and ABTS radical scavenging activity of peptide fractions, smaller-size peptides (<3 kDa) displayed considerably higher values and hence more potency than larger-sized peptides (>3 kDa). Peptide fractions with 3-10 kDa had better metal chelation and reducing power than those < 3 kDa and > 10 kDa. These findings suggest that camelina protein hydrolysates could be employed as bioactive ingredients in the formulation of functional foods and against oxidative stress.